ANALISIS PENGARUH KURS TERHADAP CURRENT ACCOUNT BALANCE DI ASEAN-6 - Deris Desmawan; Suci Hilmiati Oktari; Rizal Syaifudin; Sugeng Setyadi (LPSDI Bina Patria, 2022)
This istudy iaims itoanalyze tthedependentvariableof the icurrent iaccountbalancein iASEAN-6bysamplingbasedonannualtime-seriesdataforthe2010-2019period.Theindependent ivariables iused iin ithis istudy iare itheexchangerateasthecoreindependentvariable,then igross idomestic iproduct iand iforeign idirect iinvestmentascontrol ivariables.All idata iin ithis istudy iwere iobtained ifrom itheWorldBank.Fixedeffectmodel(FEM)paneldataanalysismethodwasused.Based ion ithe ipartial itest(t-test), ithecoreindependentvariableoftheexchangerate ihas ia isignificantieffect ion ithe icurrent iaccountbalanceinASEAN-6,aswellasthecontrolvariable,namelygrossdomesticproductandforeigndirectinvestment,whichhasasignificanteffectonthecurrentaccountbalanceinASEAN-6.Meanwhile, tthe isimultaneous itest(F-Test)shows ithat ithe iexchange irate, igross idomesticproduct iand iforeign idirect iinvestmentsimultaneously ihave ia isignificant ieffect ion ithecurrent iaccount ibalance iinASEAN-6. Keywords:CurrentAccountBalance,Exc